Bypassing the press gallery: from Howard to Hanson. Issue 1 (May 2018) - Fisher, Caroline; Marshall, David; McCallum, Kerry
Traditionally politicians have been dependent on political news media to get their message across to the public. The rise of social media means that politicians can bypass the Press Gallery and publish directly to their target audiences via Facebook, Twitter and other social media platforms. This article argues that Prime Minister John Howard's (1996–2007) use of talk back radio and early forays on YouTube were pivotal in the trend towards 'disintermediation' in Australian politics. It draws on two studies. One involving interviews with 87 key media actors from the Howard era including journalists, broadcasters, politicians and media advisers; and a second, which includes fresh interviews with contemporary press secretaries. This article examines the shift from a 'mass media logic' to a 'hybrid logic', considered from a mediatization theoretical position. We also ask important questions about the press gallery's ongoing relevance in the digital era, when politicians preside over their own social media empires.